2016
DOI: 10.1107/s2056989016005028
|View full text |Cite
|
Sign up to set email alerts
|

(E)-1-(Anthracen-9-yl)-3-(2-chloro-6-fluorophenyl)prop-2-en-1-one: crystal structure and Hirshfeld surface analysis

Abstract: In the title compund, the enone moiety adopts an E conformation. An intra­molecular C—H⋯F hydrogen bond generates an S(6) ring motif. In the crystal, mol­ecules are arranged into centrosymmetric dimers via pairs of C—H⋯F hydrogen bonds. The crystal structure also features C—H⋯π and π–π inter­actions. Hirshfeld surface analysis was used to confirm the existence of inter­molecular inter­actions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…There are four compounds that have an anthrancene-ketone substituent on the chalcone, viz. 9-anthryl styryl ketone and 9,10-anthryl bis(styryl ketone) (Harlow et al, 1975), (2E)-1-(anthracen-9-yl)-3-[4-(propan-2-yl)phenyl]prop-2-en-1-one (Girisha et al, 2016), and (E)-1-(anthracen-9yl)-3-(2-chloro-6-fluorophenyl)prop-2-en-1-one (Abdullah et al, 2016). Zainuri et al (2018c) reported the structure of (E)-1,3-bis(anthracen-9-yl)prop-2-en-1-one.…”
Section: Database Surveymentioning
confidence: 99%
“…There are four compounds that have an anthrancene-ketone substituent on the chalcone, viz. 9-anthryl styryl ketone and 9,10-anthryl bis(styryl ketone) (Harlow et al, 1975), (2E)-1-(anthracen-9-yl)-3-[4-(propan-2-yl)phenyl]prop-2-en-1-one (Girisha et al, 2016), and (E)-1-(anthracen-9yl)-3-(2-chloro-6-fluorophenyl)prop-2-en-1-one (Abdullah et al, 2016). Zainuri et al (2018c) reported the structure of (E)-1,3-bis(anthracen-9-yl)prop-2-en-1-one.…”
Section: Database Surveymentioning
confidence: 99%
“…A survey of Cambridge Structural Database (CSD, Version 5.39, last update Nov 2017; Groom et al, 2016) revealed fusedring substituted chalcones similar to the title compound. There are four compounds that have an anthracene-ketone substituent on the chalcone: 9-anthryl styryl ketone and 9,10-anthryl bis(styryl ketone) were reported by Harlow et al (1975), (2E)-1-(anthracen-9-yl)-3-[4-(propan-2-yl)phenyl]prop-2-en-1-one was described by Girisha et al (2016), while (E)-1-(anthracen-9-yl)-3-(2-chloro-6-fluorophenyl)prop-2-en-1-one was reported by Abdullah et al (2016). Zainuri et al 2018reported a structure with two anthrancene substituents on a chalcone, viz.…”
Section: Database Surveymentioning
confidence: 97%
“…There are four compounds that have an anthranceneketone subtituent on the chalcone, including 9-anthryl styryl ketone and 9,10-anthryl bis(styryl ketone) reported by Harlow et al (1975). (2E)-1-(Anthracen-9-yl)-3-[4-(propan-2-yl)phenyl]prop-2-en-1-one was reported by Girisha et al (2016), while (E)-1-(anthracen-9-yl)-3-(2-chloro-6-fluorophenyl)prop-2-en-1-one was reported by Abdullah et al (2016). Zainuri et al (2018a) reported a chalcone with two anthrancene substituents, viz.…”
Section: Database Surveymentioning
confidence: 98%